Incidence of bleeding and performance of the PRECISE-DAPT score in predicting bleeding in patients on dual antiplatelet therapy after treatment for acute coronary syndrome in Kenya - Peter Mugo; Mohamed Jeilan; Miriam Msunza; James Orwa; Mzee Ngunga (BMC Cardiovascular Disorders)
Abstract Introduction Dual Antiplatelet Therapy (DAPT) plays an important role in the secondary prevention of ischemic events after treatment for acute coronary syndrome (ACS). The long-term use of DAPT is associated with an increased risk of bleeding, which affects morbidity and mortality. Risk stratification scores have been developed to predict this risk and provide a balance against the risk of ischemic events. The aim of this study was to determine the incidence of bleeding in a cohort of patients in Kenya on DAPT and assess the performance of the PRECISE-DAPT Score in predicting the risk of bleeding. Methods This was a retrospective study conducted in three hospitals in Kenya among patients on DAPT after ACS between January 2019 and April 2022. We reviewed medical records for demographic and clinical characteristics and conducted telephone interviews to assess bleeding for patients on DAPT for a minimum period of one year. Bleeding events were categorized according to the TIMI criteria for bleeding, and the PRECISE-DAPT Score was calculated using an online calculator. The cumulative one-year incidence of bleeding was calculated and presented as frequencies and percentages. Receiver operating characteristic (ROC) analysis and C-statistics were used to quantify the ability of the PRECISE-DAPT Score to predict bleeding events, whereas calibration was estimated using the Hosmer‒Lemeshow goodness-of-fit test. Results A total of 202 patients were enrolled in the study. The study population was predominantly male (n = 156, 77.2%) and African (n = 141, 69.8%), with a median age of 61 years (IQR 52–72). Majority were admitted with ST-Elevation Myocardial infarction (STEMI) (n = 126, 62.4%) and had a mildly reduced left ventricle ejection fraction (n = 124, 61.4%). Fourteen patients (6.9%) met the TIMI criteria for bleeding, of whom 11 (5.4%) had minimal bleeding and 3 (1.5%) had minor bleeding. There was no incidence of major bleeding. The discrimination and calibration of the PRECISE-DAPT Score was good {ROC curve 0.699 (95% CI: 0.564–0.835)} and the Hosmer–Lemeshow goodness-of-fit test (Chi-square, 6.53; p = 0.588), respectively. Conclusion The incidence of bleeding was low, with the majority of patients having minimal bleeding that did not require medical intervention. The PRECISE-DAPT Score performed well in predicting bleeding in patients on DAPT.